The usage of Information and Communication Technology (ICT) knowledge among public servants. (Case study: Majlis Perbandaran Alor Gajah (MPAG) Malacca) - Mohammad, Norazlinda; Isa, Maizura (2007)
In the 21 century Information and Communication Technology (ICT) knowledge is the important assets in the organization towards the changes of the globalization. By Information and Communication Technology (ICT) knowledge it will help the growth and sustainment of the organization knowledge. Information and Communication Technology (ICT) knowledge among the public servant can improve administrative process. The value of the knowledge among the public servant will be increase. This study will examine the factors that will effect and identify the common factor contribute to it. 100 staffs in Majlis Perbandaran Alor Gajah (MPAG) will be selected randomly based on their departments. The purpose of the study to know whether the demographic factors (age, gender, level of education) influence the Usage of Information and Communication Technology (ICT) knowledge of public servant. Besides that to study the importance of Information and Communication Technology (ICT) knowledge in the overall performance of their work. Furthermore it also to identify the different group position among public servant will influences the usage of Information and Communication Technology (ICT) knowledge. The ability of the staffs in capturing and using the Information and Communication Technology (ICT) is differing from one position to another position in their job. It shows that their capability and ability to capturing and using Information and Communication Technology (ICT) knowledge is related to the performance in their task. This study will show how the job positions are interrelated to the level of information technology knowledge. Other than that is to know the level of Information and Communication Technology (ICT) knowledge among the public servant. Based on the findings the usage of ICT knowledge have significance with age, performance of the, different group position and level of ICT knowledge.